Stranger danger? Cue‐based trust in online consumer product review videos. (6th August 2021) - Pfeuffer, Alexander; Phua, Joe
Abstract: Trust is a significant factor in electronic word‐of‐mouth (eWOM) effects. Consumers often need to form judgements about others using heuristic cues when they cannot rely on previous cumulative experiences with an online entity. Drawing on the theoretical construct of cue‐based trust and signalling theory, this study aimed to identify and examine the efficacy of content attributes serving as trust cues in online consumer product review videos. A multi‐method study conducted a series of focus groups and a survey study; focus groups identified 18 content attributes intentionally provided by a content creator in product review videos that serve as trust cues. In the focus groups and the survey, six of these content attributes emerged as heuristic cues that are particularly effective at eliciting consumer trust. Findings contribute to the understanding of cue‐based trust and signalling theory in the eWOM context and hold practical implications for various stakeholders.